Analisi Tingkat Kesehatan Unit Simpan Pinjam Pada Koperasi Pegawai Republik Indonesia (Studi kasus pada Koperasi Pegawai Republik Indonesia Rumah Sakit Umum Daerah Dr. Achmad Muchtar Bukittinggi) - Zuwita Permata Sari; Marwan Marwan; Tri Kuniawati (Jurnal Ecogen, 2020)
This research aims to analyze the financial performance of USP KPRI-RSUD Dr. Achmad Muchtar Bukittinggi in 2014-2018 based on Regulation of Deputy of Supervision in Ministry of Cooperatives and SMEs Number: 06 / Per / Dep.6 / IV / 2016.This research is a type of evaluative descriptive research. The subject of this research is savings and loan units’ cooperatives of the Republic of Indonesia employees Dr. Achmad Muchtar regional public hospitals Bukittinggi and the object of this research is the financial performance. Data collection in this study uses documentation and interview methods. The data analysis technique uses in this study is evaluative descriptive analysis. The results of this study indicate that overall, the financial performance of savings and loan units’ cooperatives of the Republic of Indonesia employees Dr. Achmad Muchtar regional public hospitals Bukittinggi in 2014-2018 is in the categorized as supervision by getting an average score of 56.35.Keywords : the financial performance, cooperative savings, loans unit